On globally nilpotent differential equations - Dettweiler, Michael; Reiter, Stefan (Journal of differential equations, 2010)
In a previous work of the authors, a middle convolution operation on the category of Fuchsian differential systems was introduced. In this note we show that the middle convolution of Fuchsian systems preserves the property of global nilpotence. This leads to a globally nilpotent Fuchsian system of rank two which does not belong to the known classes of globally nilpotent rank two systems.
Gesehen am 31.01.2024